Metaheuristics for Improving Routing Efficiency in MANET Protocol. - Ben guessoum Imane; Boughezala Hamad Rania (University of Shahid Hama Lakhdar - El Oued, 2024)
This master's dissertation explores the application of a metaheuristic algorithm called MRFO (Manta Ray Foraging Optimization) for optimizing routing protocols within mobile ad hoc networks (MANETs). MANETs are a type of decentralized wireless network consisting of mobile nodes that can establish temporary connections with each other, independent of any pre-existing infrastructure. Routing protocols, a critical component of MANET functionality, comprise a set of rules and algorithms that manage the forwarding of data packets across the network. The research proposes an improved routing protocol based on MRFO, called MantaNet, to identify optimal routes for data transmission. The thesis addresses routing in MANETs as an optimization problem and provides an overview of optimization problems and techniques, including the presentation of the MRFO method. The application of MRFO in MANETs is then described, with various simulation results presented for different network scenarios. The simulation results demonstrate that the proposed method is capable of finding the optimal route and ensuring reliable and efficient data transmission in diverse network conditions, ranging from small to large scales, with reduced computational complexity. Overall, this research contributes to the understanding and enhancement of routing protocols in mobile ad hoc networks through the innovative application of the MRFO metaheuristic algorithm.تستكشف رسالة الماجستير هذه تطبيق خوارزمية ميتايورستية تسمى MRFO (Manta Ray Foraging Optimization) لتحسين بروتوكولات التوجيه داخل إعلانات الهاتف المحمول الشبكات المخصصة (MANETs). MANETs هي نوع من الشبكات اللاسلكية اللامركزية التي تتكون من من العقد المتنقلة التي يمكنها إنشاء اتصالات مؤقتة مع بعضها البعض، بشكل مستقل عن أي منها البنية التحتية الموجودة مسبقا. تعد بروتوكولات التوجيه مكونًا مهمًا لوظيفة MANET، تشتمل على مجموعة من القواعد والخوارزميات التي تدير إعادة توجيه حزم البيانات عبر الشبكة شبكة. يقترح البحث بروتوكول توجيه محسن يعتمد على MRFO، يسمى MantaNet، لتحديد الطرق المثلى لنقل البيانات. تتناول الأطروحة التوجيه في MANETs باعتبارها مشكلة التحسين وتوفر نظرة عامة على مشاكل التحسين و التقنيات، بما في ذلك عرض طريقة MRFO. ثم يتم وصف تطبيق MRFO في MANETs، مع نتائج محاكاة مختلفة المقدمة لسيناريوهات الشبكة المختلفة. وتظهر نتائج المحاكاة أن الطريقة المقترحة قادرة على إيجاد الطريق الأمثل وضمان الموثوقية والفعالية نقل البيانات في ظروف شبكة متنوعة، تتراوح من النطاقات الصغيرة إلى الكبيرة تقليل التعقيد الحسابي. بشكل عام، يساهم هذا البحث في فهم و تعزيز بروتوكولات التوجيه في شبكات الهاتف المحمول المخصصة من خلال الحلول المبتكرة تطبيق خوارزمية MRFO metaheuristic.
Master's theses: specializing in wired and non-wired communications
Keywords: MANET; MRFO; optimization; metaheuristic; Routing protocol.; شبكات المتنقلة ؛ التحسين بتجوال المانتا رايا ؛ تحسين ؛ فوق متفوقة ؛ بروتوكول التوجيه